The Concept of Holy Rus’ in Russian Literary and Cultural Tradition: Between the Third Rome and the City of Kitezh - Zabirko, Oleksandr (Entangled Religions, 2022)
The paper explores the genealogy of the concept of Holy Rus’ (or Holy Russia) in Russian literature and culture from the nineteenth century onward. An integral part of Russian sacred geography, Holy Rus’ underwent some profound semantic transformations in order to become an epitome of religious and ethnic purity in the context of Russia’s imperial expansion. Focusing on the literary manifestations of Russia’s contacts with the ethnic and religious Other as well as on its struggle with the universalist claims of the European Enlightenment, the study highlights the colonial aspects of the notion of Holy Rus’, thus questioning its potential of providing a viable ‘indigenous’ alternative to the Western epistemological hegemony. Finally, the paper offers a critical review of the present-day exploitation of Holy Rus’ as a transcendental model of both a unifying national force and inter-confessional dialogue.